International State of the Art Report - Capucha, Luís (2016)
The present report is part of the RESCuE project, an acronym that stands for Patterns of Resilience during Socioeconomic Crisis among Households. This project is coordinated by Professor Markus Promberger, from the Institute for Employment Research (IAB), in Germany. It was awarded by the 7th Framework Programme, and funded by the Community Research and Development Information Service (CORDIS). The RESCuE project involves universities and research centres from 9 different European countries – Portugal, Spain, United Kingdom, Ireland, Germany, Poland, Finland, Greece, Turkey – and, in the context of the ongoing economic and financial crisis in Europe, aims to identify and understand the coping and adjusting mechanisms and strategies of different households at risk, thus learn from the resilience of European citizens, in order to find new sustainable ways of reducing poverty risks and inform and support policy making.